Midterm outcome of proximal fibular osteotomy for medial compartment osteoarthritis- a prospective study - Singh, Ajeet (International Journal of Research in Orthopaedics, 2022)
Background: Primary osteoarthritis of knee is one of the most common degenerative conditions associated with disability. With more of varus knee medial compartment osteoarthritis is most common and early presentation. High tibial osteotomy (HTO) is technically demanding and associated with major complication like neurovascular injury, iatrogenic fracture, nonunion. Practically HTO is associated with longer bed immobilization and difficult to take bilateral condition. Methods: We treated 38 patients 54 knees with proximal fibular osteotomy for primary medial compartment osteoarthritis excluding other condition like secondary and inflammatory from January 2017 to December 2017. Pre operative assessment of patients done on standing antero-posterior (AP) X-ray and knee injury and osteoarthritis outcome score (KOOS). Post operative assessment done on opening of medial joint line space on standing AP X-ray and KOOS score. Results: Patients treated with PFO, there was change in the weight bearing axis, opening of the medial joint space, improvement in pain, functional outcome assesses with improvement in KOOS score. 8 patients experienced some catchy knee pain and swelling and deterioration of KOOS score. Conclusions: PFO is simple, cost effective and can be surgical treatment option for primary medial compartment Osteoarthritis irrespective of age, though a greater number of patients with longer follow is needed, initial results are very promising in majority of patients and few patients shows deterioration in comparison to initial results but overall patient’s satisfaction index is good.